2003
DOI: 10.1037/0033-2909.129.4.614
|View full text |Cite
|
Sign up to set email alerts
|

Religiousness and depression: Evidence for a main effect and the moderating influence of stressful life events.

Abstract: The association between religiousness and depressive symptoms was examined with meta-analytic methods across 147 independent investigations (N ϭ 98,975). Across all studies, the correlation between religiousness and depressive symptoms was -.096, indicating that greater religiousness is mildly associated with fewer symptoms. The results were not moderated by gender, age, or ethnicity, but the religiousness-depression association was stronger in studies involving people who were undergoing stress due to recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

61
683
11
36

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 939 publications
(822 citation statements)
references
References 205 publications
61
683
11
36
Order By: Relevance
“…Esses dados sugerem adequada validade discriminante para a P-DUREL. Esses dados corroboram uma metanálise de 147 estudos que demonstra uma fraca correlação entre envolvimento religioso e sintomas depressivos (r = -0,10), que aumentou para -0,15 em populações estressadas 35 . Similarmente, correlações fracas e inversas foram observadas entre sintomas ansiosos e dimensões da religiosidade.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Esses dados sugerem adequada validade discriminante para a P-DUREL. Esses dados corroboram uma metanálise de 147 estudos que demonstra uma fraca correlação entre envolvimento religioso e sintomas depressivos (r = -0,10), que aumentou para -0,15 em populações estressadas 35 . Similarmente, correlações fracas e inversas foram observadas entre sintomas ansiosos e dimensões da religiosidade.…”
Section: Discussionunclassified
“…Para determinação da validade convergente-discriminante, os coeficientes de correlação Spearman entre os escores da P-DUREL foram determinados, esperando-se a priori observar relativas sobreposições (convergência) entre os escores das dimensões da P-DUREL (correlações significativas), na ausência de redundância significativa (correlações fracas a moderadas) 21 . Com base em dados preliminares de que a religiosidade, com grande frequência, se relaciona com medidas de espiritualidade 23 e inversamente com sintomas depressivos [33][34][35][36][37][38] e ansiosos 1,39,40 , resolveu-se determinar os coeficientes de correlação de Spearman entre os escores das dimensões da P-DUREL e tais variáveis (tratadas como variáveis contínuas). O nível de significância foi de P < 0,05 (bicaudal; hipótese nula: r = 0 e hipótese alternativa: r ≠ 0).…”
Section: Análise Estatísticaunclassified
“…Currently, the associations of religiosity/spirituality and the following have been shown: mental disorders (greater general well-being 10 , lower prevalence of depression 11 , drug abuse 12 , and suicide 13 ); better quality of life 14,15,16 ; better coping with the disease 17 ; lower mortality 18,19 ; shorter hospitalization 20 ; and even better immune function. 21 In Brazil, 92.6% of the population have a religion and approximately 90% attend church regularly 22 , thus the importance of assessing the aspects of spirituality and religiosity in patients on dialysis.…”
Section: Results a N D Discussionmentioning
confidence: 99%
“…In a meta-analytic review of 147 independent effect sizes that was published in this journal, Smith, McCullough, and Poll (2003) found that religiousness (measured in a wide variety of ways) was associated with lower rates of depressive symptoms (mean effect size of r ϭ Ϫ.09, p Ͻ .000001). Moreover, this overall mean effect size obscures the fact that some measures of religiousness (e.g., positive religious coping, intrinsic religious motivation, and positive God concepts) had even stronger negative associations with depressive symptoms (i.e., mean effect sizes in the range of r ϭ Ϫ.20 to Ϫ.18), whereas measures of negative religious coping and extrinsic religious motivation were positively related to depressive symptoms (i.e., mean effect sizes Correspondence concerning this article should be addressed to Michael E. McCullough, Department of Psychology, University of Miami, P.O.…”
mentioning
confidence: 99%
“…E-mail: mikem@miami.edu Psychological Bulletin © 2009 American Psychological Association 2009 0033-2909/09/$12.00 DOI: 10.1037/a0014213 69 in the range of r ϭ .14 to .16). It is important to note that the religiousness-depression association was as strong among African Americans as it was among Americans of European descent and Northern Europeans, suggesting that the association is not limited to the White Protestants who are overrepresented in U.S. studies (Smith et al, 2003). Similarly, a 2-decades-old meta-analysis (Witter, Stock, Okun, & Haring, 1985) concluded that religiousness was positively associated with subjective well-being (mean effect size of r ϭ .16).…”
mentioning
confidence: 99%